The Influence Badminton Athlete Content on Social Media Youth Training Motivation Palopo City - Burhan, Ahmad Syarif; Hasanuddin, M. Iqbal; Takwa, Muh. Radit (Sportify Journal, 2022)
Youth sport participation is increasingly influenced by digital environments, particularly social media content featuring elite athletes that may shape adolescents’ motivation, sport identity, and training commitment. This study aimed to examine the influence of badminton athlete content consumption on social media toward youth training motivation in Palopo City. A quantitative approach with a correlational survey design was used. The participants were 108 adolescents aged 13–19 years who actively used social media and were registered as members of badminton clubs in Palopo City. The sample was selected using purposive sampling based on training activity, social media use, and voluntary participation. Data were collected using two structured Likert-scale questionnaires measuring badminton athlete content consumption and badminton training motivation. The instruments showed strong reliability, with Cronbach’s alpha coefficients of 0.876 and 0.891. Data were analyzed using descriptive statistics, normality and linearity tests, and simple linear regression at a 5% significance level. The results showed a strong positive and significant influence of badminton athlete content consumption on youth training motivation, r = 0.757, R² = 0.573, t = 11.95, p < 0.05. These findings indicate that athlete-related social media content explains 57.3% of the variance in training motivation. The study concludes that social media can serve as a strategic motivational resource in youth badminton development when used in a planned, educational, and contextually relevant manner.       Partisipasi olahraga remaja semakin dipengaruhi oleh lingkungan digital, khususnya konten media sosial yang menampilkan atlet-atlet elit yang dapat membentuk motivasi remaja, identitas olahraga, dan komitmen pelatihan. Penelitian ini bertujuan untuk menguji pengaruh konsumsi konten atlet bulu tangkis di media sosial terhadap motivasi berlatih remaja di Kota Palopo. Pendekatan yang digunakan adalah pendekatan kuantitatif dengan desain survei korelasional. Partisipannya adalah remaja berusia 13–19 tahun yang aktif menggunakan media sosial dan terdaftar sebagai anggota klub bulu tangkis di Kota Palopo berjumlah 108 orang. Sampel dipilih menggunakan purposive sampling berdasarkan aktivitas pelatihan, penggunaan media sosial, dan partisipasi sukarela. Data dikumpulkan dengan menggunakan dua kuesioner terstruktur berskala Likert yang mengukur konsumsi konten atlet bulutangkis dan motivasi latihan bulutangkis. Instrumen menunjukkan reliabilitas yang kuat, dengan koefisien Cronbach’s alpha sebesar 0,876 dan 0,891. Data dianalisis menggunakan statistik deskriptif, uji normalitas dan linearitas, serta regresi linier sederhana pada taraf signifikansi 5%. Hasil penelitian menunjukkan adanya pengaruh positif dan signifikan yang kuat konsumsi konten atlet bulutangkis terhadap motivasi latihan remaja, r = 0,757, R² = 0,573, t = 11,95, p < 0,05. Temuan ini menunjukkan bahwa konten media sosial terkait atlet menjelaskan 57,3% variasi motivasi latihan. Studi ini menyimpulkan bahwa media sosial dapat berfungsi sebagai sumber motivasi strategis dalam pengembangan bulu tangkis remaja bila digunakan secara terencana, mendidik, dan relevan secara kontekstual.